2021
DOI: 10.1039/d1ra00978h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nanoscale electroless plating procedure for bismuth and its application in template-assisted nanotube fabrication

Abstract: We outline the development of a remarkably stable electroless bismuth plating bath. Its nanofabrication potential is showcased by coating ion-track etched polymer membranes, enabling the synthesis of sub-micron diameter bismuth tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These metals are not utilized frequently, and corresponding reactions often suffer from large impurity fractions [78] and employ unusual reducers ( e. g ., thiourea, [78] Sn(II)) [79] . Selective metal deposition can be achieved through carefully balancing the metastable redox pair, as demonstrated in electroless Bi nanoplating [80] …”
Section: Plating Bath Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These metals are not utilized frequently, and corresponding reactions often suffer from large impurity fractions [78] and employ unusual reducers ( e. g ., thiourea, [78] Sn(II)) [79] . Selective metal deposition can be achieved through carefully balancing the metastable redox pair, as demonstrated in electroless Bi nanoplating [80] …”
Section: Plating Bath Chemistrymentioning
confidence: 99%
“…[79] Selective metal deposition can be achieved through carefully balancing the metastable redox pair, as demonstrated in electroless Bi nanoplating. [80] The reactivity of metal complexes can be tuned by varying their oxidation state and ligand shell. As a rule of thumb, low oxidation states are beneficial because they lessen the electron requirement for reduction and limit the number of potential intermediates (e. g., partially reduced Pt(II) forming aside elemental Pt in a Pt(IV)-based bath).…”
Section: Metal Complexmentioning
confidence: 99%
“…1b, the apparent rate constant kapp of the reaction can be determined, which amounts to 0.059 min -1 . [7] Figure 1: a) SEM images of Ir-coated ion-track etched polycarbonate membranes; b) characteristic absorbance of methyl orange after treatment with the catalyst for different times in stirred solution; c) absorbance of methyl orange/NaBH4 solution before and after passing the membrane in a flow reactor setup at 5 ml min -1 (adapted from [8]).…”
Section: Application: Degradation Of Methyl Orangementioning
confidence: 99%
“…Recently, we found that a plating bath based on the remarkably stable EDTA complex of Bi(III) in combination with borane dimethylamine (DMAB) as reducer is suitable for nanoscale Bi plating. [8] Figure 2a shows electroless Bi deposits in ion-track etched polycarbonate membranes. The amount of deposited Bi can be controlled by adjusting the deposition time.…”
Section: Synthesis: Electroless Bi Platingmentioning
confidence: 99%
See 1 more Smart Citation